2013
DOI: 10.3174/ajnr.a3673
|View full text |Cite
|
Sign up to set email alerts
|

Actinomycosis in the Mandible: CT and MR Findings

Abstract: SUMMARY:Mandibular actinomycosis is an uncommon disease. We retrospectively reviewed 6 patients with pathologically proven mandibular actinomycosis who underwent both CT and MR imaging to evaluate the characteristic imaging findings. CT results showed an irregularly marginated lesion with increased bone marrow attenuation, osteolysis, and involvement of the skin in all patients. Periosteal reaction and intralesional gas were seen in 4 patients. MR imaging results revealed low signal on T1-weighted and high sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 14 publications
0
15
0
1
Order By: Relevance
“…Dental panoramic radiography is mandatory to assess apical lesions, and computed tomography and magnetic resonance imaging may be useful to assess any extensive bone involvement . If a fluctuant abscess is present, aspiration biopsy must be conducted to examine pus for the presence of “sulfur granules”; the crushed granules are cultured anaerobically for 7 days to observe colonies of typical “molar tooth” morphology (Figure ).…”
Section: Bacterial Infectionsmentioning
confidence: 99%
“…Dental panoramic radiography is mandatory to assess apical lesions, and computed tomography and magnetic resonance imaging may be useful to assess any extensive bone involvement . If a fluctuant abscess is present, aspiration biopsy must be conducted to examine pus for the presence of “sulfur granules”; the crushed granules are cultured anaerobically for 7 days to observe colonies of typical “molar tooth” morphology (Figure ).…”
Section: Bacterial Infectionsmentioning
confidence: 99%
“…The absence of Enterobacteriaceae in all cultures made a perforation even less likely. Although intralesional gas formation in actinomycosis has previously been reported in the literature, the cause of the pneumoperitoneum in our patient remains unclear [13,1517]. Actinomyces species or concomitant bacteria may both produce gas in these rare forms of actinomycosis, but Sasaki et al reported that “intralesional” gas is specific to osteomyelitis caused by Actinomyces [15].…”
Section: Discussionmentioning
confidence: 69%
“…Although intralesional gas formation in actinomycosis has previously been reported in the literature, the cause of the pneumoperitoneum in our patient remains unclear [13,1517]. Actinomyces species or concomitant bacteria may both produce gas in these rare forms of actinomycosis, but Sasaki et al reported that “intralesional” gas is specific to osteomyelitis caused by Actinomyces [15]. Signs of bowel wall thickening on CT scan images are common in actinomycosis of the abdomen and there is generally a mass with an infiltrative aspect nearby [10].…”
Section: Discussionmentioning
confidence: 94%
“…Cervicofacial actinomycosis is a granulomatous infection that occasionally causes head and neck mass lesions. Often related to poor dental hygiene or dental manipulation, these lesions occur in the oral cavity and masticator space (25,61). These masses are often misdiagnosed as malignancy because they have a subacute clinical course and are difficult to diagnose microbiologically (25).…”
Section: Oral Cavity and Buccal Or Masticator Spacementioning
confidence: 99%
“…Radiologic findings of actinomycosis include an enhancing soft-tissue mass with a hypoattenuating center and surrounding inflammatory changes (25,26) (Fig 21). Regional lymphadenopathy is uncommon, a finding that may help distinguish the lesion from malignancy (25,61). Tuberculosis is another granulomatous differential consideration when a mass lesion is seen in the masticator space.…”
Section: Oral Cavity and Buccal Or Masticator Spacementioning
confidence: 99%